1096 Establishment and application of occupational health expenditure input-output model in iron and steel enterprise. (24th April 2018) - Shen, F; Zhang, Q; Meng, J; Xiao, S; Yuan, J; Wang, H; Tang, Y
Abstract : Introduction: Insufficient and unreasonable occupational health investment is one of the important reasons for the high rate of occupational diseases and accidents in iron and steel sector. The purpose of this study is to establish occupational health and safety investment prediction model of iron and steel manufacture for higher returns. Methods: The DEA model and input-output table were established. The detailed data of the input and output of each branch in a steel enterprise in 2015 were collected and the input and output efficiency of occupational health in each branch were evaluated through DEA method. The data were put into the DEA model and a list of relevant parameters calculation and adjustment scheme were obtained, and occupational health input and output data after adjustment and other relevant data were substituted into it to build prediction model. Results: According to the characteristics of the iron and steel enterprise's occupational health, occupational health funds input-output table have been established, which can reflect the input and output relationship among various departments (workshops) directly and clearly. In the branches of the iron and steel enterprise, the occupational health input output efficiency score of stainless steel plant and smoother was the highest, equal to 1, while the cold rolling plant had the lowest, equal to 0.759. In the cold rolling plant, only acid rolling workshop parameters met the standard of α=1, s - =0, s + =0. And the remaining four workshop could reach at 1.7044, 2.0238, 1.3152 and 1.2136 times respectively after adjusting each component according to the parameter. The adjusted data were put into the occupational input-output table and the prediction model was built. Conclusion: If the estimated annual output of a given year is known, after being converted to the total output value, the most suitable occupational health input and the largest occupational health output can be calculated.